Psychometric Validation of an Instrument for Measuring Patient Experiences with Outpatient Healthcare - Sočan Gregor; De Boer Dolf; Murko Eva; Kralj Marcel; Ropret Nina; Zaletel Metka (Sciendo, 2023)
Recently, a patient-reported experience measure (PREM) was developed in Slovenia to assess patients' experiences with outpatient specialist healthcare clinics. The aim of this study was to evaluate the psychometric properties (including factor structure, reliability, convergent validity, and response distribution) of the questionnaire.